Hubungan Pengetahuan dan Lama Kerja Dengan Ketrampilan Kader Dalam Menilai Kurva Pertumbuhan Balita di Posyandu Kelurahan Tegalsari Kecamatan Candisari Kota Semarang - - Hamariyana; Agustin Syamsianah; Eny Winaryati (Universitas Muhammadiyah Semarang, 2013)
Rising and descending children under five number who suffered growth obstacle could seen soon within short time (month) and could further research immediately what caused of it, and made design in order to take the action to overcome it as soon as possible. Growth advancement barrier of children weight observe could seen within growth curve of periodicalmeasurement result recorded and provide within KMS. One of success Posyandu program especially includes baby number and children under five who have KMS were influenced by Posyandu cadre’s role. Knowledge and cadre skill not could increase only but also descending. This case could occur because cadre less active therefore forget about mattershave been learned therefore their knowledge were descending. The high of knowledge level and cadre skill were influence by formal education, cadre course, frequency to participating within program, being active of cadre within Posyandu and their length being the cadre. Aimof this research was to found the knowledge and length period of job relationship by cadre skill in order to valuated children under five growth curve on Posyandu. This research was analytical survey type by crossectional method. This research carried out at Posyandu of Tegalsari, Candisari Subdistrict, Semarang city, from January 2011 to July 2011 about 35 cadres of posyandu on Posyandu of Tegalsari, CandisariSubdistrict, Semarang about 35 cadres. All of population unit were investigated. Sample within this research was using nonprobability sampling it was collection technique of population member to elected to be the sample. This sample technique was saturated sampling it was sample determination technique when all of population member used as the sample. Research result showed that about 48,6% of knowledge level cadre were good, 37,1% have been length being posyandu cadre about 16-20 years, whereas skill cadre in valuated children under five growth curve about 25,7%. There were no relationship between time period of work being the cadre with cadre skill in valuated children under five growth curve (p-value = 0,959), but found presence relationship of cadre knowledge level with cadre skill in valuating children under five growth curve (p-value = 0,001). Cadre in carried out posyandu activities expected could change assignment therefore within Posyandu, cadre ability in weigh, record and giving information could carried out by all of cadres and expected for cadre to be able within all of that sectors.Keywords: Knowledge, Period of work, Skill, Children under five, Cadre, Posyandu